(untitled) (KULT_online, 2014)
This book depicts the cultural practices of Muslim youth in the European context basing on ethnographic research conducted in France, Germany, and Britain. Mapping the manifestations and artefacts within genres such as music, comedy, fashion, and media, Herding conceptualizes the phenomenon as Islamic youth culture referring to a subcultural formation. On that score it reveals itself through recurring themes and similarities as well as a common framework informed by Islamic religious understanding. Islamic youth culture is conceptualized as a ‘conservative avant-garde’ movement including innovative and conventional aspects, concurrently, in the process of blending a hybrid cultural formation through Islam, global youth culture, and different national contexts. This research extensively contributes to the literatures on youth culture and subcultures; hybridity and globalization; and Islam in Europe.